Perbedaan Kemampuan Analisis Melalui Model Pembelajaran Kooperatif Tipe Pair Check dengan Make a Match - Rendika Vhalery; Vella Anggresta (Universitas Negeri Padang, 2021)
One of the cognitive domain elements in analysis ability is the ability to think to solve a problem. One way to solve this problem is by using the cooperative learning model of pair-check and